Mesenchymal stem cells prime proliferating adult neural progenitors toward an oligodendrocyte fate - Steffenhagen, Carolin; Weidner, Norbert (Stem Cells and Development, 2012)
Oligodendrogenesis encompasses lineage specification of neural progenitor cells (NPCs) and differentiation into oligodendrocytes that ultimately culminates in the myelination of central nervous system axons. Each individual process must be tightly regulated by extracellular and cell-intrinsic mechanisms, whose identities are barely understood. We had previously demonstrated that soluble factors derived from rat mesenchymal stem cells (MSCs) induce oligodendrogenesis in differentiating adult NPCs under differentiation conditions. However, since lineage specification predominantly occurs in proliferating progenitors and not necessarily during early differentiation, we investigated if soluble factors derived from MSCs are able to prime NPCs to the oligodendroglial fate already under proliferation conditions. Therefore, we analyzed the effects of a 3 weeks stimulation of adult NPCs under proliferation conditions with conditioned media derived from MSCs (MSC-CM) in terms of cell morphology, proliferation, cell-specific marker expression profile, response to growth factor withdrawal (GFW), cell-lineage restriction, and expression of glial fate determinants. While MSC-CM did not affect the proliferation rate of NPCs, it boosted the formation of 2′, 3′-cyclic-nucleotide-3′-phosphodieesterase (CNPase)- and myelin basic protein-expressing oligodendrocytes after GFW, even when cells were exposed to an astrogenic milieu. Moreover, it reinforced the proper development of oligodendrocytes, since it ensured a sustained expression of the functional marker CNPase. Finally, the presence of MSC-CM reduced the anti-oligodendrogenic determinant Id2 in proliferating NPCs, thus increasing the relative proportion of the pro-oligodendrogenic factor Olig2 expression. In summary, MSCs prime proliferating progenitors and, thus, reinforce cell fate choice and accelerate differentiation toward the oligodendrocyte lineage. The present findings underscore the potential use of MSCs in cell therapies for remyelination such as in multiple sclerosis and spinal cord injury. Moreover, they urge the identification of the oligodendrogenic activity(ies) derived from MSCs to develop novel molecular therapies for demyelinating diseases.